Hubungan Anemia dengan Hasil Belajar Siswi : Literature Review: Penelitian - Ami Dwinanda Rudeva; Ardi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Anemia is a condition when the hemoglobin level in the blood is below normal limits, so that the blood's ability to transport oxygen throughout the body decreases. This lack of oxygen can affect mental function, especially in terms of concentration and information processing while studying. This study aims to examine the relationship between anemia and learning outcomes in female students. The method used is through the Systematic Literature Review approach. The data collection process was carried out using Google Scholar to search and collect various scientific articles that discuss the topics of anemia, cognitive function, and learning outcomes. Based on the results of the review, it was found that anemia had a negative impact on the ability to think, memory, and the level of participation of female students in learning activities. This also has an impact on the low learning outcomes of female students. Therefore, special attention is needed from schools and health workers to carry out early detection and intervention for female students who experience anemia, in order to improve the quality of learning and encourage the achievement of better learning outcomes.